An Overview of antibiotic prescription after tooth extraction across dentist in Bandung City, Indonesia: A Cross-Sectional Study - Zahrah Diva Shasya; Farah Asnely Putri; Indra Hadikrishna (Odonto : Dental Journal, 2022)
Background: Tooth extraction is one of minor oral surgical procedure and antibiotics are commonly prescribed before or after the tooth extraction procedure. Antibiotic is used as therapy or to prevent infections after tooth extractions. Recent studies discovered that misuse of antibiotics by dentists has been an issue nowadays. The purpose of this study is to investigate the frequency and varieties of antibiotics post tooth extraction used by dentists in Bandung City.Method: This study uses a quantitative descriptive method with a cross-sectional approach using a questionnaire. The samples in this study are general dentists and specialists in Bandung. The questionnaire was sent to dentists using proportionate stratified random sampling. Result: The most frequently used antibiotics in Bandung City are Amoxicillin 500 mg (83,1%) and Clindamycin (24,3%). Most respondents prescribed antibiotics after tooth extractions for 5 days.Conclusion: A small percentage of Dentists in Bandung City still prescribed antibiotics in conditions that do not always require antibiotics, such as simple post-extraction, irreversible pulpitis, and reversible pulpitis. Broad-spectrum antibiotics are more commonly prescribed to prevent infections. Furthermore, antibiotic usage after simple tooth extraction needs to be done by considering the patient’s condition, diagnosis, and difficulty level of extraction.